Designing Lesson Plans in CLT Method (Eurasian Research Bulletin, 2022)
This article focuses on creating effective lesson plans and presenting their main principles which should be taken into consideration all the time in Communicative language teaching method(CLT). Besides that, implementing matters of CLT method in Uzbekistan higher education universities, especially in teaching ESP students.